The Correlation between Impacted Third Molar and Blood Group - Hanie Ahmadi; Alireza Ebrahimi; Farhad Ghorbani (Hindawi Limited, 2021)
Background. Blood type is among the most important genetical characteristics of any individual and is shown to be correlated with the development of a variety of illnesses including dental diseases. Finding the association of ABO and Rh blood groups and impacted tooth is important in order to predict which population is more vulnerable to grow impacted third molars that could lead to making better intervention. The present investigation tried to take a small step in that regard, by evaluating the correlation between ABO and Rh blood groups and the most commonly impacted tooth, bony impacted third molars among Iranian individuals. Methods. The investigation was done retrospectively on patients who were referred to the Department of Oral Radiology, Shiraz University of Medical Science, Shiraz, Iran. The patients were classified according to their blood groups, and 40 patients were randomly selected for each blood type. Therefore, the impaction of their third molars was evaluated, and statistical analyses were done in order to find any association. Results. A total of 320 participants contributed to the study; 136 (42%) were males and 184 (57%) were females. The mean age was 29 ± 6 years. Among all participants, 205 (64%) had no impacted third molar, 26 (8%) had one impacted third molar, 43 (13%) had 2 impacted third molars, 5 (1%) had 3 impacted third molars, and 41 (12%) had 4 impacted molars. Conclusion. According to the results of the present study, nearly one out of three individuals has at least an impacted third molar in the Iranian population, being more prevalent in individuals between 20 and 30 years old. The evaluation of the relationship between the blood group and impacted third molar revealed that blood groups have no association with the impacted third molars. However, more studies with higher and diversified participants should be done to find comprehensive results.